The Future Role of Physician Associates in Ophthalmology Services - Yu Jeat Chong; Matthew Azzopardi; Darren S. J. Ting (British and Irish Orthoptic Journal)
As a response to increasing pressures on hospital eye services, the Royal College of Ophthalmologists (RCOphth) has started exploring the integration of physician associates (PAs) into ophthalmology as a means of expanding the ophthalmic workforce while maintaining high standards of care. However, the proposal has sparked a discussion within the ophthalmic community regarding the role of PAs in a specialty that already benefits from a well-established and specialized multidisciplinary team. Concerns have been raised about their short generalist training, which may not fully prepare them for the complexities of ophthalmic care, as well as the high cost of their integration compared to other healthcare professionals. Given these issues, upskilling existing allied health professionals and leveraging digital health innovations could be more effective solutions in addressing workforce shortages. The Royal College of Ophthalmologists (RCOphth), having endorsed the pilot scheme, bears the burden of proof to demonstrate the efficacy and value of PAs in this specialized field, ensuring that any workforce expansion aligns with the high standards expected in ophthalmic care.